The Spanish bookbinding in the Royal academies - Carpallo-Bautista, Antonio; Burgos-Bordonau, Esther (Qualitative and Quantitative Methods in Libraries; Vol 7 No 3 (2018): September 2018 Issue, 2019)
The research project that we are now announcing has been granted by the Ministry of Economy, Industry and Competitiveness of Spain and deals with "The Spanish Bookbinding in the Royal Academies: binders, workshops and different typologies (18th -20th centuries)". The main goal of our project is to search, analyze and identify all the bookbinders who worked for the eight more relevant Royal Academies in Madrid. To carry out this research, we have to look at all the account books, expenses and minute books conserved during (18th - 19th and mid. 20th centuries). Later we will identify all the bookbindings that are located in the different Academies. The final aim of the research is to fill out the gap left in the Spanish scientific production of an essential part of the History of Books and Bookbinding.